Karakteristik Kualitas Perairan Berdasarkan Parameter Fisik Di Pelabuhan Perikanan Jeruju Kalimantan Barat - Nuraya, Tia; Sari, Dahlia Wulan; Harfinda, Elliska Murni (Program Studi Ilmu Kelautan FMIPA Universitas Tanjungpura, 2024)
Water quality is one aspect for marine, estuarine and terrestrial organisms. Poor water quality can also reduce the ecosystem in the area. Therefore, this study aims to determine the condition of water quality based on physical and chemical parameters that are very important to do. The study was conducted at the Jeruju Fishing Port, West Kalimantan. The physical parameters taken were temperature, salinity, pH, current, brightness, and tides. The results of the study showed that the average temperature at the location was 28 ° C, salinity was 0 PSU, pH was 6.26, classified as acidic and approaching normal, currents ranged from 0.1 cm/s including calm currents, brightness values in the waters of the Jeruju TPI ranged from 17.5 - 27.5 cm and the type of tide at the location was a diurnal type of tide where there was one high tide and one low tide. These results indicate that the quality of the waters is still relatively good.